Pipe Stacking Optimization and Sea Fastening Analysis of Linepipe Transport - Daniel Mohammad Rosyid; Raditya Danu Riyanto; Carlo Jonathan Sihombing (International Journal of Offshore and Coastal Engineering, 2020)
Subsea pipeline is a system comprised of multiple linepipes that are welded when installed on location used to distribute fluid such as oil and natural gas. Fabricated linepipes are to be stacked on cargo barge and transported to the installation location. This operation takes significant time and involves numerous linepipes. Optimization needs to be done to make sure the transport operation is executed efficiently. Optimization attempt was done using data from Double Joint Linepipe Transport Operation of Tangguh Expansion Project by Saipem Indonesia. Parameters considered during the optimization process include linepipe qualities during stacking, cargo barge strength and stability, and sea fastening property strength. Roark’s Formulas for Stress and Strain formulas are used in pipe stacking analysis to find stacking limit for each type of linepipes. Stability analysis is done by using DNVGL-ST-N001 as a guide and Maxsurf software for modelling. SACS software is used to analyzed sea fastening properties with guidance from DNVGL-ST-N001. Finally, optimization is done using a multi-criteria optimization method by using values from each analysis as parameters. Optimization results find that pipe stacking method using side support is 8.41% more optimal than standard pipe stacking method from Saipem Indonesia.